Effect of responsive graft length on mechanical toughening and transparency in microphase-separated hydrogels. Issue 43 (28th August 2019) - Mussault, Cécile; Guo, Hui; Sanson, Nicolas; Hourdet, Dominique; Marcellan, Alba
Abstract : Poly( N -isopropylacrylamide) grafts in a hydrophilic covalently crosslinked polymer network enable efficient T -responsive toughening. Here, we show that graft length is a key-parameter to enhance stiffness and fracture (bulk and adhesion) properties. Abstract : Effective remote control of mechanical toughening can be achieved by using thermo-responsive grafts such as poly( N -isopropylacrylamide) (PNIPAm) in a hydrophilic covalently cross-linked polymer network. The weight ratio of PNIPAm grafts in the network may impart such a thermo-responsive mechanical reinforcement. Here, we show that the network topology – especially graft length – is likewise crucial. A series of covalently cross-linked poly( N, N -dimethylacrylamide) (PDMA) gels grafted with PNIPAm side-chains of different lengths were designed and studied on both sides of phase separation temperature T c, at a fixed overall polymer concentration of 16.7 wt% and constant PDMA/PNIPAm weight ratio. Phase-separated PNIPAm organic micro-domains were expected to act as responsive fillers above T c and to generate a purely organic nanocomposite (NC). In contrast to conventional NC gels where dissipative processes take place at the solid nanoparticle/matrix interface, here dissipation originates from the disruption of the filler itself by the unravelling of the PNIPAm grafts embedded in collapsed domains. Results show that PNIPAm graft length is a key parameter to enhance – reversibly and on-demand – the mechanical response. The longer the graft is, the more effective the mechanical toughening is. Interestingly, for long PNIPAm grafts, above T c, the hydrogels combine perfect transparency together with both increased stiffness and fracture toughness (up to 150 J m −2 ) at constant macroscopic volume. As a proof of concept, stimuli-responsive adhesion and shape-memory properties were designed to probe the inter-chain bridging efficiency (in bulk or bridging the interface).